2022
DOI: 10.3390/genes13061031
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of mRNAs and Long Non-Coding RNAs Expression of Oviduct That Provides Novel Insights into the Prolificacy Mechanism of Goat (Capra hircus)

Abstract: Artificial directional selection has replaced natural selection and resulted in trait differences across breeds in domestic animal breeding. However, the molecular mechanism by which the oviduct regulates litter size remains largely elusive in goats during the follicular phase. Accumulating data have linked lncRNAs to reproductive activities; however, little is known about the modulation mechanism in the oviduct. Herein, RNA-seq was used to measure mRNA and lncRNA expression levels in low- and high-fecundity g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“… 52 AMPK is reported to be involved in autophagy of granulosa cells and oocytes, which regulates follicle development, 53 and AMPK in the fallopian tube may contribute to embryonic development, spermatocyte DNA damage repair, and ovarian steroid hormone production. 54 …”
Section: Discussionmentioning
confidence: 99%
“… 52 AMPK is reported to be involved in autophagy of granulosa cells and oocytes, which regulates follicle development, 53 and AMPK in the fallopian tube may contribute to embryonic development, spermatocyte DNA damage repair, and ovarian steroid hormone production. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Cortisol and steroid hormones are known to regulate ovarian cell proliferation, apoptosis, folliculogenesis, and folliculogenesis [41]. Animal multifertility is closely related to the occurrence and development of follicles, especially directly related to the number of ovulatory dominant follicles [42]. In another study on the regulation of follicular development in black goats, it was also found that the conversion of progesterone and testosterone occurs in the process of ovarian steroidogenesis, which is one of the most important hormonal pathways known for follicular maturation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has started uncovering the amounts of protein and mRNA expression in the same sample to better understand probable molecular mechanisms and identify reliable biomarkers of specific biological processes [ 24 , 74 ]. In this study, we utilized transcriptomic data generated in the oviduct from the same tissue sample, which we previously published [ 75 , 76 ], to complement the proteomic analysis. Comparing the two phases, our transcriptomics and proteomics results showed that many more transcripts can be identified than proteins in the oviduct.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput RNA sequencing (RNA-seq) was conducted following our previously published studies [ 75 , 76 ] and using the same oviduct samples as in protein extraction. Briefly, total RNAs from the 20 oviduct tissues in follicular and luteal phases were extracted by TRIzol reagent (Invitrogen, Carlsbad, CA, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%